Inventarisasi Cacing Parasitik pada Ikan Kembung di Perairan Teluk Banten dan Pelabuhan Ratu (THE HELMINTH PARASITES INVENTORY OF RASTRELLIGER SP. FROM BANTEN BAY AND PELABUHAN RATU BAY) - Indaryanto, Forcep Rio; Wardiatno, Yusli; Tiuria, Risa (Jurnal Veteriner, 2015)
The monitoring of health and disease in a fish is important as parasitism plays a central role in fishbiology. Parasitism is a ubiquitous phenomenon in the marine environment and it is probable that allmarine fishes are infected with parasites. The aims of the research were to inventory the helminth parasitesof Rastrelliger sp. from Banten Bay and Pelabuhan Ratu Bay. As many as 25–30 of fish samples werecollected using gill net and examined for helminth parasites. The helminth parasitic calculated intensityand prevalence. The helminth parasites of Rastrelliger sp. were found Lechitocladium angustiovum (digenea:Hemiuridae), Lecitochirium sp. (digenea: Hemiuridae), Prodistomum orientalis (digenea: Lepocreadiidae)and Anisakis typica (nematodes: Anisakidae), with 90.12% of prevalence. L. angustonum was dominancehelminth parasites found in fish. There was no difference on parasites found in R. kanagurta and R.brachysoma wich were of Restrellinger genus. The location not appear have no significant after on helminthparasitic infection as they have a same genetic stock. Anisakis species in Java sea have a same genetipewith Anisakis typical and was not zoonotic parasite categories.
Keywords: helminth parasites, Rastrelliger spp., Banten Bay, Pelabuhan Ratu Bay